Asymptotic behavior of higher-order neutral difference equations with general arguments - Chatzarakis, G. E.; Khatibzadeh, H.; Miliaras, G. N.; Stavroulakis, I. P. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We study the asymptotic behavior of solutions of the higher-order neutral difference equation$$Δm[x(n)+cx(τ(n))]+p(n)x(σ(n))=0,N∍m≥2,n≥0,$$where $τ (n)$ is a general retarded argument, $σ(n)$ is a general deviated argument, $c ∈ R; (p(n)) n ≥ 0$ is a sequence of real numbers, $∆$ denotes the forward difference operator $∆x(n) = x(n+1) - x(n)$; and $∆^j$ denotes the jth forward difference operator $∆^j (x(n) = ∆ (∆^{j-1}(x(n)))$ for $j = 2, 3,…,m$. Examples illustrating the results are also given.